Interaction Between Ag+, Nucleobases and Nucleotides in Solution - Cheng, Howard; Chowdhury, Ashraf; Huq, Fazlul (Asian Journal of Chemistry, 2010)
The interaction between silver ion and adenine, guanine and guanosine monophosphate (GMP) has been followed by UV difference spectroscopy using the technique of continuous variation and high pressure liquid chromatography, combined with molecular modeling. Ag+ is found to combine with adenine to form three adducts with binding ratios (Ag+ : Adenine) of 2:1 and 1:1. It combines with guanine to form 1:1 adduct. It combines with GMP to form two adducts having the binding ratios (Ag+ : GMP) of 2:1 and 1:1. The proposed structures of the complexes formed have been optimized based on molecular mechanics and semi-empirical calculations using HyperChem 7.